Peran Dinas Pariwisata terhadap Promosi di Desa Wisata Letvuan Paradise Kabupaten Maluku Tenggara - Nurria Salam Difinubun; Ida I Dewa Ayu Raka Susanty; Rahma Gusmawati Tammu (Universitas Kristen Indonesia Toraja, 2025)
This study aims to determine the role of the Tourism Office in promoting Letvuan Paradise Tourism Village and what obstacles are faced by the Tourism Office of Southeast Maluku Regency in carrying out promotions in Letvuan Paradise Tourism Village, Southeast Maluku Regency. This research method uses a qualitative descriptive method. Data collection techniques used observation, interviews, and literature studies. The results of the study indicate that the Southeast Maluku Regency Tourism Office plays a significant role in promoting the Letvuan Paradise Tourism Village through facilitation, mentoring, and collaboration with various parties. Promotion is carried out through official social media, annual events, and efforts to include Letvuan Paradise in the National Event Calendar (CEN). Promotion in the tourism sector is a means of communication to introduce a tourist destination and build a positive image, thereby increasing the number of visitors and providing economic benefits to the surrounding community. In addition to Hawang Cave, promotion also highlights local potential such as arabusta coffee, Japanese bunkers, and community culture. The Tourism Office also supports Pokdarwis and MSMEs through training and involvement in various activities. This encourages community and village government participation in tourism promotion. Obstacles faced include limited infrastructure, budget, and the use of digital technology. Overall, the Tourism Office plays a significant role in building the image of Letvuan Paradise, but sustainable development still requires infrastructure improvements, consistent promotion, and community independence.